An Approach for Model Querying-by-Example Applied to Multi- Paradigm Models - Radjenovic, Alek; Paige, Richard (Electronic Communications of the EASST, 2013)
Scenarios for industry-scale multi-paradigm modelling involve analysis,transformation, or fine-grained manipulation of models. These models are often treatedwholly or in part as trees (e.g. XML or XMI documents, or source code). However,existing facilities for accessing and manipulating models as trees is limited. We present anovel approach to model querying-by-example, treating models as trees. The approachabstracts away from platform-specific concerns (e.g. XML), and exploits tree-basedpatterns in expressing queries; the results of queries are also trees, thus providing meansto compose (conjoin) queries without requiring intermediate manipulations.